Biocomputing 2010 2009
DOI: 10.1142/9789814295291_0037
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Genome-Wide Haplotype Polymorphism by Combined Use of Mendelian Constraints and Local Population Structure

Abstract: Data from current gene-disease association studies motivate changes to existing haplotype inference methodologies. Many datasets are now comprised of both pedigree and population data so it is desirable to incorporate both sources of information when inferring haplotypes. The availability of high-density SNP data also makes it possible to determine and use the precise locations of recombination events. Our proposed method reconstructs haplotype structure on a genome-wide level by jointly using the information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
3
1
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…nucleotide adjacent dependency [5]) may be used to address this problem. Although the recombination hotspots analyzed in this paper was obtained experimentally, our approach is not limited to this type of data and we can computationally estimate recombination rates from sequence polymorphism data in large scale, either based on LD structure [2], [13] or pedigree structure [14]. In addition, as our results of GO analysis suggested that epigenetic mechanism is shared by top candidate genes, we will follow up with studies of epigenetic interaction between histone and DNA as mediated by PRDM9 and other predicted proteins.…”
Section: Discussionmentioning
confidence: 99%
“…nucleotide adjacent dependency [5]) may be used to address this problem. Although the recombination hotspots analyzed in this paper was obtained experimentally, our approach is not limited to this type of data and we can computationally estimate recombination rates from sequence polymorphism data in large scale, either based on LD structure [2], [13] or pedigree structure [14]. In addition, as our results of GO analysis suggested that epigenetic mechanism is shared by top candidate genes, we will follow up with studies of epigenetic interaction between histone and DNA as mediated by PRDM9 and other predicted proteins.…”
Section: Discussionmentioning
confidence: 99%
“…We assume that the genotypes of both parents are not available and infer the IBD status for each pair of siblings. We then compare the results of IBD changing breakpoints with the recombination breakpoints inferred by our previous algorithm Mendelian constrained maximum likelihood (MML) (Li et al , 2010) using genotypes of both parents and children. The second dataset is a pedigree of size 15, among which only seven members are typed.…”
Section: Resultsmentioning
confidence: 99%
“…To systematically evaluate the correctness of inferred IBD sharing regions of all sibling pairs, we compare our result with that inferred by our previous algorithm MML (Li et al , 2010), which is a Mendelian law-based method and use genotypes of both parents and children. MML infers the inheritance pattern by using Mendelian constraints between parents and children.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A description of the Beagle software is available at http://faculty.washington.edu/browning/beagle/beagle.html. [The method proposed by Li et al (23) can be used to infer the haplotypes for sibpair data. ]…”
Section: Methodsmentioning
confidence: 99%